Accounting Information as a Mediation of Business Experience on Business Success - Sri Trisnaningsih; Alifiah Wulansari Mustofa; Bagus Maulana Hendrawan (Future Science, 2021)
The purpose of this study is to determine and analyze the effect of business experience on business success through the use of accounting information as an intervening variable. The quantitative method used in this study was a population of 163 coffee shop SMEs in Surabaya and 62 samples were obtained through purposive sampling. Research data was obtained directly by distributing questionnaires. Furthermore, the data were analyzed by path analysis through IBM SPSS Statistics 22 software. This study shows that business experience has a positive effect on the use of accounting information, business experience and the use of accounting information has a positive effect on business success. However, business experience does not have a positive effect on business success through the use of accounting information, which means that the use of accounting information by MSME actors is not able to mediate the effect of business experience on business success.